Influence of Board Characteristics and Ownership Concentration on Corporate Sustainability Growth among Listed Manufacturing Companies in Nigeria: Array - Adebayo, Aderemi Olalere; Onikoyi, Idris Adegboyega; Kareem, Tajudeen Ayofe; Lamidi, Wasiu Adebayo (Acta Universitatis Danubius. Œconomica, 2021)
The influence of corporate governance on the manufacturing firms’ sustainable growth during the financial crisis period cannot be overemphasized. Hence, this study was carried out find out the kind of influence the corporate governance mechanisms have on the corporate sustainable growth in Nigeria. The population of the study consists of listed manufacturing companies, and a sample size of 30 manufacturing firms was selected using a purposive sampling technique based on convenience, covering a time period of five financial years (2011 to 2020). The regression method was used to analyze the data collected through secondary sources. The result showed that board size, board composition, ownership concentration, board independence, and firm size had a positive relationship with corporate sustainable growth while leverage had a negative relationship with corporate sustainable growth. Thus, the study showed that corporate governance exercises a positive influence on corporate sustainable growth and the study recommended that listed manufacturing firms put in place a larger board structure that encompasses people of different backgrounds, skills, and experience in order to help the companies move forward during difficult times; and a good board structure that makes provision for the presence of independent directors needs to be maintained, to checkmate the management so that all the decisions taken by the management will be the ones to achieve the company’s ultimate goal